2014
DOI: 10.1109/thms.2014.2309662
|View full text |Cite
|
Sign up to set email alerts
|

Programming Robots to Express Emotions: Interaction Paradigms, Communication Modalities, and Context

Abstract: Robots are beginning to be used in many fields, including health care, assistive industries, and entertainment. However, we believe that the usefulness of robots will remain limited until end-users without technology expertise can easily program them. For example, the wide range of situations in which robots must express emotions as well as the differences in people with whom robots interact require that emotional expressions be highly customized. Thus, end users should have the ability to create their own rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Through Laban Movement Analysis (LMA), Wei and Zhao 2016) integrated four emotional patterns into robot behaviours using motion planning. Interestingly, (Manohar and Crandall, 2014) studied how novice people program robot's behaviors to express emotions through recorded audios and gestures and then recognized them. The study found that non-verbal emotions were not easy to discern than those expressed via verbal channels.…”
Section: Nao As a Support For Affective Computing Researchmentioning
confidence: 99%
“…Through Laban Movement Analysis (LMA), Wei and Zhao 2016) integrated four emotional patterns into robot behaviours using motion planning. Interestingly, (Manohar and Crandall, 2014) studied how novice people program robot's behaviors to express emotions through recorded audios and gestures and then recognized them. The study found that non-verbal emotions were not easy to discern than those expressed via verbal channels.…”
Section: Nao As a Support For Affective Computing Researchmentioning
confidence: 99%
“…In addition, SR has gained popularity during the previous years and is expected to be used in a variety of social applications. They have produced therapy interventions for autistic children [15], [16], exercise trainers, and provided specialized education and assistance to the elderly [17].…”
Section: Introductionmentioning
confidence: 99%